Geographical analysis of the temporary space behavior of sound intensity in barrio Escalante, San José, Costa Rica. November 2021 to March 2022 - Guillén Montero, Douglas Alberto (Revista Geográfica de América Central., 2024)
Noise Pollution is considered one of the biggest health risks in modern society worldwide, partly caused by city dynamics. Although its recognition as a health Hazard is recent and its effects have become considered a health problems, actions, and policies to combat it are not yet common in big cities. This article shows the results of a geographical analysis where this type of pollution was evaluated in Barrio Escalante, the objective was to analyze the spatial-temporal behavior of sound intensity during October 2021 to March 2022. In order to achieve that objective, a quantitative study was developed with  sound level meter measurements. This allowed  measuring the intensity of the sounds in different places of Escalante, in two periods: day and night. Decibels were then classified by cycle according to their intensity on a scale of one to five. This is how the general sound index (GSI) was subsequently obtained and so the sound intensity plane of the study area.